Dietary modulation of human milk bioactives is associated with maternal FUT2 secretor phenotype: an exploratory analysis of carotenoids and polyphenol metabolites - Fiecke, Chelsey; Crimmins, Meghan; Hameed, Ahsan; Sims, Clark; Williams, D. Keith; Bode, Lars; Martinez, Audrey; Andres, Aline; Ferruzzi, Mario G. (Frontiers in Nutrition, 2024)
Introduction: Maternal diet modifies profiles of human milk oligosaccharides (HMOs), carotenoids, and polyphenols in human milk (HM). However, substantial variability in profiles exists between women, highlighting the complexity of non-dietary factors modulating these profiles. The objective of this study was to carry out a secondary analysis exploring the effect of maternal diet on HM carotenoids and polyphenols and relationships between dietary modulation of HM bioactives (carotenoids, polyphenols, oligosaccharides) and maternal α1,2-fucosyltransferase 2 (FUT2) secretor phenotype. Methods: In this pilot study, 16 exclusively breastfeeding women with obesity were enrolled between 4 and 5 months postpartum. The women were provided a 4-week meal plan consistent with the 2020 Dietary Guidelines for Americans (DGA). HM was collected for 24 hr at baseline and post-intervention. Maternal FUT2 secretor phenotype was determined by 2’-fucosyllactose concentration in HM (non-secretor: < 100 nmol/ml; secretor:  100 nmol/ml). Concentrations of carotenoids and HMOs were determined by LC and polyphenol metabolites by UPLC-MS/MS. Results: Thirteen women completed the study (6 secretors, 7 non-secretors). The change in HM concentrations of the HMOs lacto-N-tetraose (LNT, p = 0.007), lacto-N-fucopentaose II (LNFP II, p = 0.02), difucosyllacto-N-tetraose (DFLNT, p = 0.003), and disialyllacto-N-tetraose (DSLNT, p = 0.003) and polyphenol metabolites 4-hydroxybenzoic acid (4-HBA, p = 0.08) and ferulic acid (p = 0.02) over the intervention time frame was differentially associated with maternal secretor status. 4-HBA and ferulic acid positively correlated with HMOs LNT and DSLNT (rrm = 0.82-0.90, p = 0.03-0.06) for secretors but not for non-secretors. Only secretors demonstrated a negative correlation between 4-HBA and DFLNT (rrm = -0.94, p = 0.001). Discussion: The influence of maternal diet on composition of HMOs and polyphenol metabolites in HM differs based on maternal secretor status. Consideration of non-dietary factors is needed to evaluate differences in response of HM bioactives to dietary modulation.